1997
DOI: 10.1088/0953-8984/9/39/001
|View full text |Cite
|
Sign up to set email alerts
|

The importance of edge states in the quantum Hall regime of the organic conductor

Abstract: We report measurements of the longitudinal magnetoresistance and magnetization of in pulsed magnetic fields of up to 50 T and temperatures down to 400 mK, using samples of different purity. Below 2 K the amplitude of the Shubnikov - de Haas oscillations in is found to decrease dramatically with falling temperature. This effect is shown to coincide with quasipersistent eddy current resonances in the magnetization, which are a signature of the quantum Hall effect. Evidence is provided for the existence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
62
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 32 publications
8
62
0
Order By: Relevance
“…3,4 While is between Landau levels, the carriers involved in charge transport cannot perform the closed orbits necessary to cause changes in the Hall resistivity xy , which therefore remains ''frozen'' at a constant value; 5,6 it has been shown that the plateaux in xy thus produced correspond to a manifestation of the quantum Hall effect ͑QHE͒. [6][7][8][9][10][11] At the same fields, the resistivity component ʈ Ϸ 1 2 ( xx ϩ yy ) exhibits deep minima 7,9,10 and the interplane resistivity zz shows large maxima. 4 In this paper, we describe measurements of the Hall potential in ␣-(BEDT-TTF) 2 TlHg(SCN) 4 in this high-field range, made using an analog of the Corbino geometry ͑Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 While is between Landau levels, the carriers involved in charge transport cannot perform the closed orbits necessary to cause changes in the Hall resistivity xy , which therefore remains ''frozen'' at a constant value; 5,6 it has been shown that the plateaux in xy thus produced correspond to a manifestation of the quantum Hall effect ͑QHE͒. [6][7][8][9][10][11] At the same fields, the resistivity component ʈ Ϸ 1 2 ( xx ϩ yy ) exhibits deep minima 7,9,10 and the interplane resistivity zz shows large maxima. 4 In this paper, we describe measurements of the Hall potential in ␣-(BEDT-TTF) 2 TlHg(SCN) 4 in this high-field range, made using an analog of the Corbino geometry ͑Fig.…”
mentioning
confidence: 99%
“…9 The current saturation is thought to be due to mechanisms such as Zener tunneling between Landau levels at the sample edges. 10,23 This leads to a dissipation of the induced current and thus to breakdown of the QHE. 9,10 The maximum Hall potential energy drop eV H between the center and the perimeter of the sample is therefore limited by the Landau-level spacing ប c .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, since both the gapped one-particle DOS and the derivative of the Fermi-Dirac (FD) distribution function are symmetric aboutm 6 h, both h andm (irrespective of sign) have an equivalent detrimental effect on the stability of the CDW condensate. Given that the magnitude ofm ϳ 1 2h v c ϳ 1 meV [20,21] at fields of 23 T in the M K salt (wherehv c is the cyclotron energy of the 2D pocket) is directly comparable with D 0 ϳ 1.2 meV (estimated using the BCS relation), m should clearly have quite a pronounced effect on these materials. Furthermore, a large body of papers, concerning measurements of quantum oscillatory effects and angular magnetoresistance oscillations within the low temperature, low magnetic field (LTLF) phase of these salts, support a picture in which the CDW (or SDW) is commensurate throughout [19,22,23].…”
Section: National High Magnetic Field Laboratory Lanl Ms-e536 Los mentioning
confidence: 99%
“…Metals with a quasi-two-dimensional ͑2D͒ Fermi surface ͑such as organic metals 4,5 ͒ may serve as model crystals due to the relatively simple picture of their magnetoquantum oscillations. Not only the fundamental frequency and amplitude ͑cyclotron mass͒ but also the precise wave form of oscillations has become the object of investigations, [6][7][8] including magnetoquantum oscillations with spin-split structure. [9][10][11][12][13][14] These investigations give valuable information about the more complex Fermi surface in quasi-2D organic metals containing both closed and open parts.…”
Section: Introductionmentioning
confidence: 99%